The Role of NAD+ in Myocardial Ischemia-induced Heart Failure in Sprague-dawley Rats and Beagles - Pei, Zuowei; Yang, Chenguang; Guo, Ying; Dong, Min; Wang, Fang (Current Pharmaceutical Biotechnology, 2024)
Introduction: Nicotinamide adenine dinucleotide (NAD+) participates in various processes that are dysregulated in cardiovascular diseases. Supplementation with NAD+ may be cardioprotective. However, whether the protective effect exerted by NAD+ in heart failure (HF) is more effective before acute myocardial infarction (MI) or after remains unclear. The left anterior descending arteries of male Sprague Dawley rats and beagles that developed HF following MI were ligated for 1 week, following which the animals were treated for 4 weeks with low, medium, and high doses of NAD+ and LCZ696. Methods: Cardiac function, hemodynamics, and biomarkers were evaluated during the treatment period. Heart weight, myocardial fibrosis, and MI rate were measured eventually. Results: Compared with the HF groups, groups treated with LCZ696 and different doses of NAD+ showed increased ejection fractions, fractional shortening, cardiac output, and stroke volume and decreased end-systolic volume, end-systolic dimension, creatine kinase, and lactic dehydrogenase. LV blood pressure was lower in the HF group than in the control group, but this decrease was significantly greater in the medium and high NAD+ dose groups. Conclusion: The ratios of heart weight indexes, fibrotic areas, and MI rates in the CZ696 and medium and high NAD+ dose groups were lower than those in the HF group. Medium and highdose NAD+ showed superior positive effects on myocardial hypertrophy, cardiac function, and myocardial fibrosis and reduced the MI rate.
Keywords: NAD+